2019
DOI: 10.3390/safety5040070
|View full text |Cite
|
Sign up to set email alerts
|

Driving Behaviour in Depression: Findings from a Driving Simulator Study

Abstract: Depression is characterized by mental, emotional and executive dysfunction. Among its symptoms, sleep disturbance and anxiety are very common. The effects of depression and its treatment may have an impact on driving behaviour. In order to evaluate driving performance in depression, 13 patients and 18 healthy controls completed questionnaires and scales and were tested in a driving simulator. Driving simulator data included lateral position (LP), speed and distance from the preceding vehicle. History of collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Our results showed that the total score and the score of all MDBQ subscales were higher in the group with depression, which means that depression is negatively correlated with driving performance. Similar to our findings, previous studies have found that depression (independent of the severity) is associated with driving impairment (5,12).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that the total score and the score of all MDBQ subscales were higher in the group with depression, which means that depression is negatively correlated with driving performance. Similar to our findings, previous studies have found that depression (independent of the severity) is associated with driving impairment (5,12).…”
Section: Discussionsupporting
confidence: 93%
“…Most road accident studies have focused on socio-demographic characteristics and general personality as well as driving skills (11). While few studies have addressed driving performance considering depression and anxiety, their main purpose has often been the effects of medications, specifically antidepressants, and benzodiazepines, on road accidents (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of epidemiological research propose that depression has an impact on driver aggression, it's difficult to draw any firm conclusion from the previous studies (20). For example, interestingly, a recent preliminary driving simulator study with a small sample size (13 patients vs. 18 healthy controls) investigating behaviors of depressive patients reported that depression was negatively related to aggressive driving (36). About one third of depressive patients especially those with comorbid axis-2 disorders (e.g., antisocial personality disorder, borderline personality disorder) display anger attacks that highly respond to 88 antidepressant treatment (37).…”
Section: Discussionmentioning
confidence: 99%
“…Research in the broader field of road safety focuses primarily on the simulation of driver behavior, possibly of specific situations in traffic, using suitable case studies (typically from selected urban agglomerations) [25,26], or applications of simulation tools (software), such as MSC Adams [27][28][29], that enable the simulation of vehicle movement dynamics. The usage of simulations can well describe the technical impacts on the vehicle or infrastructure, including its effect on cargo behavior.…”
Section: Literature Reviewmentioning
confidence: 99%